Democracy, Oil and Politics in the Niger Delta: Linking Citizens' Perceptions and Policy Reform - Jinadu, L. Adele et al (Centre for Advanced Social Science, 2007)
This book is an adaptation of a Project Report, Popula Perceptions of Oil Governance in the Niger Delta: Case Studies of Abia, Akwa Ibom and Cross River States, submitted by the Centre for Advanced Social Science (CASS), Port Harcourt to the Open Society Initiative for West Africa (OSIWA), Darkar, Senegal. The study is aimed at enabling the CASS, Port Harcourt, Nigeria to undertake in the period July 2004 - October 2006, policy-related applied research, dissemination and advocacy activities on the allocation and uses of public sector oil-derived resources that flowed, since the return of democratic civilian rule in May 1999, into the following states in Nigeria's Niger Delta: Abia, Akwa Ibom and Cross River during the period.
Keywords: Non-Fiction; Oil and Politics